Role of paraspinal mapping before transforaminal epidural injections for lumbar radiculopathy - GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2021)
Objectives: This study aims to investigate whether electromyography (EMG) including paraspinal mapping (PM) and specific clinical findings before the injection have a predictive role on the results in patients undergoing unilateral transforaminal epidural steroid injection (TFESI). Patients and methods: In this prospective study, a total of 46 patients (19 males, 17 females; mean age: 44.0 +/- 10.8 years; range, 23 to 60 years) with unilateral L5 root compression confirmed by physical examination, EMG and lumbar MRI between March 2013 and January 2014 were included. The patients underwent L5 TFESI. After the injection, they were examined at 1 h, three weeks, and three months. Results: The clinical findings and presence of acute involvement on EMG were not predictive for TFESI results; however, the patients with lower scores for the L5 segment in PM benefited more from the injection, compared to patients with higher scores for the L5 segment in PM. Conclusion: In patients with very clearly defined L5 radiculopathy, PM EMG can give us an idea about the effectiveness of L5 TFESI.
Keywords: Lumbar radiculopathy; paraspinal mapping; transforaminal epidural injection; STEROID INJECTIONS; NEEDLE ELECTROMYOGRAPHY; MUSCLE DENERVATION; DISC HERNIATION; SPINAL STENOSIS; PAIN; PREDICTORS